Changes in Physiological Levels of Cortisol and Adrenocorticotropic Hormone upon Hospitalization Can Predict SARS-CoV-2 Mortality: A Cohort Study. (25th February 2022) - Ahmadi, Iraj; Estabraghnia Babaki, Hamideh; Maleki, Maryam; Jarineshin, Hashem; Kaffashian, Mohammad Reza; Hassaniazad, Mehdi; Kenarkoohi, Azra; Ghanbarnejad, Amin; Falahi, Shahab; Kazemi Jahromi, Mitra; Ghaneialvar, Hori; Sohrabipour, Shahla
Abstract : There is some indication that coronavirus disease 2019 (COVID-19) causes hypothalamic-pituitary-adrenal axis insufficiency. However, being on glucocorticoids makes it difficult to fully investigate this axis, especially in patients with severe COVID-19. We aimed to discover if there was a connection between blood total cortisol and adrenocorticotropic hormone (ACTH) levels and mortality in patients with COVID-19. In Iran, 154 hospitalized patients with COVID-19 were studied in a prospective cohort study. ACTH and cortisol levels in the blood were measured on the first or second day of hospitalization. Most patients (52.6 vs. 47.4%) were men over 50 years old (55.8%), and 44.4% had an underlying illness. Serum cortisol and plasma ACTH medians were 15.6 ( μ g/dl) and 11.4 (pg/ml), respectively. 9.09% of the patients died. Cortisol levels were substantially lower in those who died (11.3  μ g/dl) than in patients who were discharged (16.7  μ g/dl, P < 0.01 ), while ACTH levels were unaffected. The most important factors determining mortality, according to the logistic model, were blood cortisol levels, the existence of an underlying disease, and the use of a mechanical ventilator. Cortisol levels that rose by one-unit correlated with a 26% lower risk of mortality. Comorbidities and mechanical ventilation increased the risk of death by 260 and 92 times, respectively. It can be concluded that in patients with COVID-19, a low cortisol level is linked to a high risk of mortality. Patients may sometimes have relative primary adrenal insufficiency. To judge and decide on therapeutic interventions, more reliable and long-term follow-up studies are required.